2022
DOI: 10.1091/mbc.e21-07-0370
|View full text |Cite
|
Sign up to set email alerts
|

The mitospecific domain of Mrp7 (bL27) supports mitochondrial translation during fermentation and is required for effective adaptation to respiration

Abstract: We demonstrate here that mitoribosomal protein synthesis, responsible for the synthesis of oxidative phosphorylation (OXPHOS) subunits encoded by mitochondrial genome, occurs at high levels during glycolysis fermentation and in a manner uncoupled from OXPHOS complex assembly regulation. Furthermore, we provide evidence that the mitospecific domain of Mrp7 (bL27), a mitoribosomal component, is required to maintain mitochondrial protein synthesis during fermentation, but is not required under respiration growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 43 publications
(104 reference statements)
0
24
0
Order By: Relevance
“…When the glucose is exhausted from the media, the yeast cells start to transit from the fermentative metabolism to the respiratory metabolism with drastic changes in the expression of tricarboxylic acid cycle enzymes and components of the mitochondrial electron transport chain ( 57 ). It was recently demonstrated that mitoribosomal protein synthesis occurs at high levels during glucose fermentation, which depends on bL27 mitochondria-specific C-terminal extension and its binding partner Mam33p ( 58 ), as mentioned before; it is also required for COX1 translation and adaptation to the diauxic shift ( 27 ). As it was already described for mam33 mutants, we investigated whether, besides Cox1p synthesis deficiency, the overexpression of Mrx9p would also impact the transition from fermentative to respiratory metabolism.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…When the glucose is exhausted from the media, the yeast cells start to transit from the fermentative metabolism to the respiratory metabolism with drastic changes in the expression of tricarboxylic acid cycle enzymes and components of the mitochondrial electron transport chain ( 57 ). It was recently demonstrated that mitoribosomal protein synthesis occurs at high levels during glucose fermentation, which depends on bL27 mitochondria-specific C-terminal extension and its binding partner Mam33p ( 58 ), as mentioned before; it is also required for COX1 translation and adaptation to the diauxic shift ( 27 ). As it was already described for mam33 mutants, we investigated whether, besides Cox1p synthesis deficiency, the overexpression of Mrx9p would also impact the transition from fermentative to respiratory metabolism.…”
Section: Resultsmentioning
confidence: 80%
“…Improper adaptation to the diauxic shift together with destitute Cox1p translation in fermentative conditions was also observed in mam33Δ mutants together with the loss of optimal COX1 splicing ( 27 ); indeed, Mam33p has multiple functions: it chaperones newly imported mitoribosomal proteins to ensure proper assembly of the mitoribosome ( 11 ), interacts with bL27 mitospecific domain and controls optimal mitochondrial translation under glucose ( 58 ), and together with Mrx6p and Pim1p regulates mtDNA copy number ( 83 ). The phenotypes resemblance between mam33 deletion and MRX9 excess suggests that Mrx9p may interfere in Mam33p function.…”
Section: Discussionmentioning
confidence: 99%
“…Mrp7 contains both a C-terminal ‘mitospecific’ domain and an N-terminal L27 domain (Figure 4B ). This latter domain exhibits high conservation with the prokaryote ribosomal L27 protein ( 48 ). All our mutations resided within an unstructured N-terminal stretch of the L27 region that reaches into the peptidyl transferase centre (PTC) of the mitoribosome (Figure 4B ) ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The position of Mrp7/bL27m within the mitochondrial ribosome may make this protein a prime candidate to serve as a molecular conduit for translational regulation. We have previously reported that truncation of the C‐terminal mitospecific region of Mrp7/bL27m causes differential effects depending on the metabolic environment of the cell, with an inhibition of translation observed under glucose/fermentation conditions, but not under glycerol/respiration conditions [15]. Although translational output appeared normal in the C‐terminal mrp7 mutants under respiratory conditions, the resulting newly synthesized proteins displayed a reduced competency to subsequently assemble into productive OXPHOS complexes, suggesting the fidelity and/or pacing of translation had been compromised in these C‐terminal mrp7 mutants [15].…”
mentioning
confidence: 99%
“…We have previously reported that truncation of the C‐terminal mitospecific region of Mrp7/bL27m causes differential effects depending on the metabolic environment of the cell, with an inhibition of translation observed under glucose/fermentation conditions, but not under glycerol/respiration conditions [15]. Although translational output appeared normal in the C‐terminal mrp7 mutants under respiratory conditions, the resulting newly synthesized proteins displayed a reduced competency to subsequently assemble into productive OXPHOS complexes, suggesting the fidelity and/or pacing of translation had been compromised in these C‐terminal mrp7 mutants [15]. We speculated that the C‐terminal region of Mrp7/bL27m through communication to the N‐terminal end of Mrp7/bL27m located in the PTC has the capacity to influence the integrity of the mitotranslational process.…”
mentioning
confidence: 99%